(untitled) (Research, Society and Development, 2022)
Introduction: The increase in air pollution in recent decades is notorious, especially in urban centers, where there has been a disorderly process of industrialization and population growth. Residents of urban centers are exposed to pollutants that negatively influence organic systems, primarily the cardiorespiratory system. Residents of coastal areas enjoy a cleaner environment. Our objective was to evaluate the influence of different concentrations of atmospheric pollutants on respiratory variables during maximal stress test. Methodology: Eighty men aged 40 years and over were evaluated, divided into 2 groups: Residents of São Paulo, Group 1 and residents of Baixada Santista, Group 2. Participants underwent a cardiorespiratory test, determining their physical fitness level (VO2max) and the variables: ventilatory equivalent of carbon dioxide (VE/VCO2), pulmonary ventilation (VE) and ventilatory equivalent of oxygen (V/VO2). Data were presented as mean ± standard deviation. STATISTIC 9.0 was used for the analysis and the one-way variance test was applied to compare respiratory data between groups. Results: The groups were similar in peak oxygen consumption: Group 1= 17.5±0.04 ml/kg/min and Group 2, 18.3±0.08 ml/kg/min. Group 1 presented altered ventilatory responses during the cardiorespiratory test when compared to Group 2: (VE=80±0.3 ml and VE=70±0.2 ml, p=0.004), (VE/VCO2=35.7±0, 3 units and VE/VCO2=31.7±0.1 units, p=0.003) and (V/VO2=36.5±0.2 units and V/VO2=31.6±0.1units, p=0.03 Conclusion: Individuals residing in São Paulo have decreased respiratory efficiency when compared to residents of coastal regions during maximal effort test.